Anniversary edition of the Roman Law textbook and handbook (Academic Journal of Internal Affairs, 2021)
It is quite extraordinary, and even unprecedented in both the Hungarian and foreign legal literature, that a textbook or handbook - with the exception of one - appears in twenty-five further developed, ie revised and expanded editions. This event, which can rightly be considered a festive moment, occurred in September 2020 in the case of the work ‘History and Institutions of Roman Law’ (Földi & Hamza, 2020), written by academician Gábor Hamza and head of the department András Földi. The textbook, which was awarded a prize in 2000, is popularly preferred not only by law students, Romanists and civilians, but also by lawyers, as it describes the history of Roman law and some of its legal institutions in an exemplary, thorough and detailed manner, with particular emphasis on its impact on existing rights.
Keywords: book review; Roman Law; textbook